Determinants of Customer Satisfaction and Customer Loyalty Over City Market Citra Raya - Shinta Shinta; Tantri Yanuar Rahmat Syah; Dimas Angga Negoro (Penerbit Kemala Indonesia, 2020)
Trade in Indonesia at the moment cannot be denied if the competition is getting tougher. City Market Citra Raya is traditional markets due to there are transactions between sellers and buyers. City Market Citra Raya here sells a daily necessity needed by consumers with a modern market concept that has facilities that are more in line with other traditional markets. In this study, we use SEM analysis (Structural Equation Model) to analyze customer need. Here, the questionnaire is distributed over 125 correspondents and consisting of a scale of one to five. The results in this study is determining a factors such as company image, service quality and price did not affect the increase in perceived value, customer satisfaction and customer loyalty. However, on the other hand, the perceived value of customer satisfaction and customer loyalty are significant influenced. Thus, in this study shows that sellers must focus on perceived value to get customer satisfaction offered to customer loyalty.